Identifiability for a Class of Discretized Linear Partial Differential Algebraic Equations. (13th April 2011) - Cantó, Begoña; Coll, Carmen; Sánchez, Elena
Abstract : This paper presents the use of an iteration method to solve the identifiability problem for a class of discretized linear partial differential algebraic equations. This technique consists in replacing the partial derivatives in the PDAE by differences and analyzing the difference algebraic equations obtained. For that, the theory of discrete singular systems, which involves Drazin inverse matrix, is used. This technique can also be applied to other differential equations in mathematical physics.